2002
DOI: 10.1103/physrevd.66.124008
|View full text |Cite
|
Sign up to set email alerts
|

Self-dual Lorentzian wormholes inn-dimensional Einstein gravity

Abstract: A family of spherically symmetric, static and self-dual Lorentzian wormholes is obtained in n-dimensional Einstein gravity. This class of solutions includes the n-dimensional versions of the Schwarzschild black hole and the spatial-Schwarzschild traversable wormhole. Using isotropic coordinates we study the geometrical structure of the solution, and delineate the domains of the free parameters for which wormhole, naked singular geometries and the Schwarzschild black hole are obtained. It is shown that, in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…On general grounds, it has recently been shown that the amount of exotic matter needed at the wormhole throat can be made arbitrarily small thereby facilitating an easier construction of wormholes [21]. Lorentzian wormholes in spacetimes with more than four dimensions were analyzed by several authors [22][23][24]. In particular, wormholes in Gauss-Bonnet gravity were considered in Ref.…”
mentioning
confidence: 99%
“…On general grounds, it has recently been shown that the amount of exotic matter needed at the wormhole throat can be made arbitrarily small thereby facilitating an easier construction of wormholes [21]. Lorentzian wormholes in spacetimes with more than four dimensions were analyzed by several authors [22][23][24]. In particular, wormholes in Gauss-Bonnet gravity were considered in Ref.…”
mentioning
confidence: 99%
“…In order to construct a traversable Schwarzschild Wormhole we must maintain the radial component of the metric and require that the redshift function has no horizons. We can also construct a generalized version of the Schwarzschild Wormhole, considering a linear shape function with the form b(r) = (1 − β)r 0 + βr, where β is a constant parameter and the β = 0 being the particular case of the Schwarzschild wormhole, also being considered a particular case of a self-dual wormhole with a null energy density [20,21]. A consequence of the β parameter is the presence of a increase or deficit of the solid angle at the asymptotic limit, depending on whether β is positive or negative.…”
Section: Introductionmentioning
confidence: 99%
“…Roughly speaking, the matter violates the weak/null energy conditions called 'exotic matter' [11] at least in a neighborhood of the wormhole throat. Such strange object exists both in the static [12][13][14][15] as well as dynamic [16][17][18][19][20][21] cases, and sustained by a single fluid component. Thus, minimize the use of exotic matter is always a subject of an intense research area.…”
Section: Introductionmentioning
confidence: 99%